Prediction of the adherence to sports practice of young Ecuadorians based on the perception of the coach’s interpersonal style - Heredia-León, Diego Andrés; Manzano-Sánchez, David; Gómez-Mármol, Alberto; Valero-Valenzuela, Alfonso (Frontiers in Psychology, 2023)
Based on the framework of the self-determination theory, the present study aimed to test a predictive model in the Ecuadorian sports context by using autonomy support as a trigger, which was mediated by basic psychological needs and later by autonomous motivation. This procedure was used to predict the intention to be physically active and was carried out on 280 athletes from the province of Azuay (Ecuador) aged between 12 and 20 years (M = 15.28; SD = 1.71). Different scales were used to measure the perception of the interpersonal style of autonomy supported by the coach. The scales employed included the degree of satisfaction of basic psychological needs, motivation to practice sports, and intention to be physically active. A structural equation analysis revealed that perceived autonomy support positively predicted basic psychological needs, which in turn positively predicted autonomous motivation and, as a result, the athletes’ intentions to be physically active. It was concluded that coaches’ support for the interpersonal style of autonomy can benefit the development of basic psychological needs as well as autonomous motivation, which in turn can increase young athletes’ intentions to be physically active. Future research is also recommended to verify this predictive model and to encourage further experimental studies in which coaches promote autonomy support for athletes intending to increase their adherence to practising sports.